Commodity Futures Trading Education Through Digital Platforms to Enhance Financial Literacy of the Community: Edukasi Perdagangan Berjangka Komoditi Melalui Platform Digital untuk Meningkatkan Literasi Keuangan Masyarakat - Adelia Yevi Wahyuni; Hery pudjoprastyono (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
The low financial literacy of Indonesians remains a major challenge, especially in distinguishing between legal and illegal investments. This condition encourages the need for adaptive and accessible financial education. This activity aims to increase public understanding of the legality, risks, and investment strategies in commodity futures trading through a digital-based educational approach. The implementation was carried out online through the Zoom platform, involving interactive material delivery by broker representatives from PT Victory International Futures, and equipped with live trading simulations using the MetaTrader5 application. The results showed that participants gained a more comprehensive understanding of the legal and technical aspects of futures trading, and demonstrated an improved ability to analyze risks and make wiser investment decisions. Digital-based education has proven to be effective in reaching a wide range of people and has a positive impact on improving a sustainable financial literacy culture.